FTA Highlight No.11 – REDD+: Combating Climate Change with Forest Science - Martius, C.; Duchelle, Amy E. (CGIAR Research Program on Forests, Trees and Agroforestry, 2021)
The climate change battle has many fronts; protecting the world’s remaining forests is a major one. Land-use change, including deforestation, contributes 10–12% of global emissions (IPCC 2019), and the REDD+ framework (reducing emissions from deforestation and forest degradation) has been seen as a way to promote both climate and sustainable development benefits. Now enshrined in the Paris Agreement, the central offer of REDD+ consists of results-based payments to forest-rich countries for protecting forests and avoiding carbon emissions. The challenges associated with this approach are large, and a diversity of actors is needed to make it a success, including researchers. Could science contribute to make REDD+ more efficient, more effective and more equitable? Scientists with CIFOR’s Global Comparative Study on REDD+ (GCS REDD+) have been analyzing REDD+ for the past 12 years. GCS REDD+ is the largest global research program of its kind and a major component of the CGIAR Research Program on Forests, Trees and Agroforestry (FTA). With dozens of national and subnational REDD+ initiatives and several hundred local projects underway, GCS REDD+ has looked at the range of approaches, analyzed conditions — from policy to land rights to forest monitoring capacity — and produced a bedrock of evidence and analysis across 22 countries. This ensures that policymakers and practitioner communities have the evidence they need to design and implement REDD+ with effective, cost-efficient and equitable outcomes.